Peliyanan terhadap Difabel dalam Novel Des Aveugles, Karya Hervé Guibert (1985) - Azmie, Alvia Marata; Udasmoro, Wening; Firmonasari, Aprillia (Pusat Studi Wanita dan Keluarga UGM, 2024)
The process of “othering” in literary works has been widely researched. However, most the research on othering in literary works have focused more on group identities, such as race or religion. Othering process for people with disabilities are rarely discussed. The article written by Hervé Guibert entitled Des Aveugles (The Blind People) published in 1985, contains aspects about the life of people with visual disabilities. However, these people are positioned as actors who behave evilly in the novel. The author describes the characters with visual disabilities as people who are passionate and like to kill and finally they die at the end of the story. Female character also experiences a more tragic death than the male characters. This clarifies gender positions and hierarchies in the story. Therefore, this article attempts to examine the process of othering for people with disabilities related to gender hierarchies in the novel. The theory of subalternity is used as a lens to read the othering process. Meanwhile, the content analysis of the story is used as method of analysis.